2007
DOI: 10.1016/j.ejcts.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel somatosensory evoked potentials and cerebrospinal proteins: indicators of spinal cord injury in thoracoabdominal aortic aneurysm surgery

Abstract: Peroperative multilevel SSEP has a high specificity in detecting spinal cord ischemia but does not identify all patients with a postoperative vulnerable spinal cord. Biochemical markers in CSF increase too late for intraoperative monitoring but GFAp is promising for identifying patients at risk for postoperative delayed paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 15 publications
0
31
1
Order By: Relevance
“…GFPa in this study was found to increase in patients with neurological damage but not in those without. This finding of increases in GFPa was further reinenforced by a study from the Safi group where GFAp increased before or in parallel to onset of symptoms in the patients with delayed paraplegia [31]. However, although these biomarkers show excellent probability for use during TAAA repair they currently require 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 biochemical laboratory analysis which and requires time, expensive equipment and specialist expertise, not conductive to a real time sensor which could be used intra-operatively.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…GFPa in this study was found to increase in patients with neurological damage but not in those without. This finding of increases in GFPa was further reinenforced by a study from the Safi group where GFAp increased before or in parallel to onset of symptoms in the patients with delayed paraplegia [31]. However, although these biomarkers show excellent probability for use during TAAA repair they currently require 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 biochemical laboratory analysis which and requires time, expensive equipment and specialist expertise, not conductive to a real time sensor which could be used intra-operatively.…”
Section: Discussionmentioning
confidence: 60%
“…However, although there is a good correlation to spinal cord ischaemia and rises in CSF lactate, there is a lag between its rise and development of CSF lactate [25]. There is now considerable interest with respects to specific biomarkers that can be biochemically analysed and are more sensitive to spinal cord ischaemia than lactate [26][27][28][29][30][31]. In particular, interest has arisen in the area of protein level monitoring, and so the aim of this work is to determine the ability of EM wave sensors to measure varying quantities of protein.…”
mentioning
confidence: 99%
“…10 GFAP on the other hand has been reported to reach peak levels after 24 h in ischemic SCI. 28,29 To date, we are not aware of published studies that have reported NFH concentrations in the CSF of human SCI patients, although Casha and colleagues at the University of Calgary have measured NFH in the CSF of patients enrolled in their prospective randomized trial of minocycline for acute SCI. 5,30 A recent study, however, used 25 swines in a model that mimics blast-induced traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the titles, abstract and the full text resulted in the inclusion of 18 articles. Twelve studies investigated biomarkers in humans [22][23][24][25][26][27][28][29][30][31][32] and six studies investigated biomarkers in animals. [33][34][35][36][37][38] Relatively few studies have been performed in which biomarkers in serum and/or CSF after SCI were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] In addition, the release of the biomarker S-100b, neurofilament light chain protein (NFL), and Glial fibrillary acidic protein (GFAP) in CSF was investigated in another study in which 39 patients underwent TAAA surgery. 31 Glial fibrillary acidic protein is a filament protein localized predominantly in astroglial At 6 h after surgery, increased levels of S-100b (Po0.001) were identified in two patients with post-operative SCI.…”
Section: 36mentioning
confidence: 99%